A pH-induced conformational switch in a tyrosine kinase inhibitor identified by electronic spectroscopy and quantum chemical calculations. Issue 1 (December 2017) - Khattab, Muhammad; Wang, Feng; Clayton, Andrew
Abstract Tyrosine kinase inhibitors (TKIs) are a major class of drug utilised in the clinic. During transit to their cognate kinases, TKIs will encounter different pH environments that could have a major influence on TKI structure. To address this, we report UV-Vis spectroscopic and computational studies of the TKI, AG1478, as a function of pH. The electronic absorption spectrum of AG1478 shifted by 10 nm (from 342 nm to 332 nm) from acid to neutral pH and split into two peaks (at 334 nm and 345 nm) in highly alkaline conditions. From these transitions, the pKa value was calculated as 5.58 ± 0.01. To compute structures and spectra, time-dependent density functional theory (TD-DFT) calculations were performed along with conductor-like polarizable continuum model (CPCM) to account for implicit solvent effect. On the basis of the theoretical spectra, we could assign the AG1478 experimental spectrum at acidic pH to a mixture of two twisted conformers (71% AG1478 protonated at quinazolyl nitrogen N(1) and 29% AG1478 protonated at quinazolyl nitrogen N(3)) and at neutral pH to the neutral planar conformer. The AG1478 absorption spectrum (pH 13.3) was fitted to a mixture of neutral (70%) and NH-deprotonated species (30%). These studies reveal a pH-induced conformational transition in a TKI.